2008
DOI: 10.1007/s00431-008-0850-7
|View full text |Cite
|
Sign up to set email alerts
|

Parental perception of weight and weight-related behaviour in 2- to 4-year-old children in the eastern part of the Netherlands

Abstract: In the data-analysis and the results section (underneath table 2) it should be: a linear regression analysis was done with the Z-score of the BMI of the child as dependent variable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…In a Dutch study among preschool children, 54.4 % of underweight children were perceived by their parents as thinner then their peers [6]. In our study, only 11.5 % of underweight children were perceived as such by their parents.…”
Section: Discussionmentioning
confidence: 82%
“…In a Dutch study among preschool children, 54.4 % of underweight children were perceived by their parents as thinner then their peers [6]. In our study, only 11.5 % of underweight children were perceived as such by their parents.…”
Section: Discussionmentioning
confidence: 82%
“…Another study on parental perception in the Netherlands reported rates similar to those in our study. 40 This underlines that classification of overweight is difficult for mothers throughout the society. Others reported that mothers who underestimate may be in denial and may not want to recognise the overweight problem.…”
Section: Discussionmentioning
confidence: 99%
“…Most researchers have found that parents tend to underestimate their child's weight, especially if the child's BMI was in the overweight or obese category (Baughcum et al 2000, Goodman et al 2000, Etelson et al 2003, Maynard et al 2003, Boutelle et al 2004, Adams et al 2005, Carnell et al 2005, Genovesi et al 2005, Jeffrey et al 2005, Eckstein et al 2006, Fisher et al 2006, Skelton et al 2006, Akerman et al 2007, Wald et al 2007, Watkins et al 2007, Muhammed et al 2008, West et al 2008, De La et al 2009, Warschburger & Kr€ oller 2009, Juliusson et al 2010, Luttikhuis et al 2010, Manios et al 2010, Perrin et al 2010, Tschamler et al 2010, Vuorela et al 2010, Christensen 2011, Hearst et al 2011. A few researchers found that parents overestimate their child's weight despite a normal BMI; one study took place in the Netherlands (Bossink-Tuna et al 2009) and one study took place in China (Wen & Hui 2010).…”
Section: Recognition Of Body Sizementioning
confidence: 99%
“…Parental recognition of physical appearance can be defined as a parent's recognition that the child was visually too large (e.g. round face or large belly) (Jain et al 2001, Rich et al 2005, Goodell et al 2008, could not fit into clothing for their age (Jain et al 2001, Jackson et al 2005, Goodell et al 2008, Booth et al 2009, Garrett-Wright 2010), or that the child is larger than his or her peers (Borra et al 2003, Jackson et al 2005, He & Evans 2007, Booth et al 2009, Bossink-Tuna et al 2009, Garrett-Wright 2010, Vuorela et al 2010.…”
Section: Recognition Of Body Sizementioning
confidence: 99%
See 1 more Smart Citation